Lost and found heir - Wood, Joss (Wood, Joss. Dynasties: DNA dilemma., 2022)
Venture capitalist Garrett Kaye has received the offer of a lifetime--become the CEO of a billion-dollar company...but only if he acknowledges he's heir to his recently discovered birth family. To keep his mind off his choices, he lets his attraction to smart, headstrong mixologist Jules Carson sweep him away. But will "no strings" turn into the ties that bind as he faces the impossible choice between his birthright and his future?